2013
DOI: 10.1631/jzus.b1200096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaCl treatments on glucosinolate metabolism in broccoli sprouts

Abstract: Abstract:To understand the regulation mechanism of NaCl on glucosinolate metabolism in broccoli sprouts, the germination rate, fresh weight, contents of glucosinolates and sulforaphane, as well as myrosinase activity of broccoli sprouts germinated under 0, 20, 40, 60, 80, and 100 mmol/L of NaCl were investigated in our experiment. The results showed that glucoerucin, glucobrassicin, and 4-hydroxy glucobrassicin in 7-d-old broccoli sprouts were significantly enhanced and the activity of myrosinase was inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 30 publications
9
46
0
1
Order By: Relevance
“…The content of intact aliphatic and indole glucosinolates in the inflorescences of broccoli cultivars Nubia, Naxos and Parthenon has also revealed differential response to salinity treatments (Dominguez Perles et al, 2011). In another work aimed to improve health promoting glucosinolates in edible sprouts suggested that glucoraphanin content decreased significantly, indole glucosinolates neoglucobrassicin, 4-hydroxyglucobrassicin and glucobrassicin were reported to decrease by 40 and 80 mm NaCl and increase by 100 mM NaCl application in 7d old broccoli sprouts germinated under different NaCl doses (Guo et al, 2013). Different from above mentioned studies, our work aimed to determine the influence of salinity on glucosinolates in broccoli seedlings representing earlier developmental stages.…”
Section: Resultsmentioning
confidence: 99%
“…The content of intact aliphatic and indole glucosinolates in the inflorescences of broccoli cultivars Nubia, Naxos and Parthenon has also revealed differential response to salinity treatments (Dominguez Perles et al, 2011). In another work aimed to improve health promoting glucosinolates in edible sprouts suggested that glucoraphanin content decreased significantly, indole glucosinolates neoglucobrassicin, 4-hydroxyglucobrassicin and glucobrassicin were reported to decrease by 40 and 80 mm NaCl and increase by 100 mM NaCl application in 7d old broccoli sprouts germinated under different NaCl doses (Guo et al, 2013). Different from above mentioned studies, our work aimed to determine the influence of salinity on glucosinolates in broccoli seedlings representing earlier developmental stages.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation might be the NaCl-stimulation of other radical scavenging compounds biosynthesis, such as isothiocyanates and glucosinolates. Yuan et al (2010) found that the total glucosinolate contents in 5-and 7-day-old radish sprouts treated with 100 mM NaCl increased by 50% and 127%, respectively; Guo et al (2013) also, reported that the content of the isothiocyanate sulforaphane in 7-day-old broccoli sprouts treated with 100 mM NaCl was 2.1 times higher than in the control.…”
Section: Radical Scavenging Capacitymentioning
confidence: 97%
“…The glucosinolate content varies depending on genetic and environmental factors, and is modulated by external signals such as sugar (Miao et al, 2013) and phytohormones (Yuan et al, 2009;Sun et al, 2012;Wang et al, 2012;Guo et al, 2013a;2013b;Huseby et al, 2013;Kim et al, 2013;Zang et al, 2015). Glucose is not only the basal carbon and energy source but also a signaling molecule having regulatory effects throughout the life cycle of plant (Sheen, 2014).…”
Section: Introductionmentioning
confidence: 99%